2021
DOI: 10.3390/jcm10112393
|View full text |Cite
|
Sign up to set email alerts
|

Bone Lengthening with a Motorized Intramedullary Nail in 34 Patients with Posttraumatic Limb Length Discrepancies

Abstract: The Fitbone® motorized nail system has been used to correct limb length discrepancies (LLD) for several years. This study focuses on its application in posttraumatic limb lengthening surgery, its outcome and challenges. Materials and methods: A prospective, single center study was conducted between 2010 and 2019 in patients treated with motorized lengthening nails. The inclusion criteria were symptomatic LLD of 20 mm or more. An imaging analysis was done using TraumaCad® software (Brainlab AG, Munich, Germany)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 35 publications
3
13
1
Order By: Relevance
“…Retrospectively, we would refrain from using a lengthening nail in those cases and recommend a hexapod frame. This emphasizes the importance of patient selection, as previously indicated by Teulières et al ( 12 ).…”
Section: Discussionsupporting
confidence: 73%
“…Retrospectively, we would refrain from using a lengthening nail in those cases and recommend a hexapod frame. This emphasizes the importance of patient selection, as previously indicated by Teulières et al ( 12 ).…”
Section: Discussionsupporting
confidence: 73%
“…However, many studies have concluded that external fixators are undesirable due to their lengthy application time, which can effortlessly lead to complications such as pin site infection and knee stiffness. Other procedures and equipment, such as limb lengthening with high distraction rates, bifocal limb lengthening, intramedullary nails without the need for external fixation, and motorized internal lengthening nails, have been developed to decrease the external fixation duration [ 1 , 3 5 , 9 , 16 ]. However, restoration of posttraumatic limb length discrepancy is not only conducted in major hospitals, and many primary hospitals do not adopt the abovementioned new equipment due to the high costs.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Teulières et al applied motorized intramedullary nails to treat 34 patients with posttraumatic limb length discrepancies. The mean lengthening was 37.5 ± 19 mm for the femur, and the mean healing index was 84.6 ± 62.5 days/cm [ 3 ]. They thought bone lengthening with a motorized intramedullary nail device for posttraumatic LLD was considered a safe and effective therapeutic technique.…”
Section: Discussionmentioning
confidence: 99%
“…LD are often associated with functional impairment of the affected extremity [ 1 ]. LD can arise from a variety of medical conditions (congenital or acquired due to trauma, tumor, infection as well as iatrogenic and idiopathic origin) [ 2 , 3 ]. Limb reconstruction is the art of treating LD and improving the functionality of the limb no matter the available resources [ 4 ].…”
Section: Introductionmentioning
confidence: 99%